Analysis of the Freshwater Ornamental Fish Marketing System in Makassar City, South Sulawesi - Asriany Asriany; Mauli Kasmi; Yusri Muhammad Yusuf (Citakonsultindo, 2023)
This study aims to identify the ornamental fish marketing system in the city of Makassar, which includes: identifying the forms of ornamental fish marketing channels, determining the roles and functions of ornamental fish marketing institutions, analyzing the marketing margin of ornamental fish, and assessing whether the marketing of ornamental fish in Makassar is efficient. The ornamental fish marketing channels in Makassar consist of 3 forms of channels: Marketing Channel I consists of cultivators, collector traders, retail traders (raisers), and end consumers, where cultivators and collector traders are located outside of Makassar. Marketing Channel II consists of cultivators, collector traders, retail traders (raisers), and end consumers, where cultivators are located outside of Makassar, while collector traders are local traders, in this case, located in Makassar. Marketing Channel III consists of cultivators, retail traders (raisers), and end consumers, where cultivators are located in Makassar. The marketing functions that occur in ornamental fish marketing are based on exchange functions in the form of sales activities conducted by all levels of marketing institutions, and purchasing activities conducted by all marketing institutions except for cultivators. Based on physical functions in the form of storage activities, they are conducted by all marketing institutions and collection activities are only conducted by marketing institutions such as collector traders (large suppliers). Packaging activities are conducted by all marketing institutions, while transportation activities are conducted by all marketing institutions. Meanwhile, based facility functions in the form of sorting and standardization activities, are conducted by all marketing institutions. Market information activities, financing, and risk-bearing occur in all marketing institutions. Based on the calculation of the marketing margin and the efficiency level of ornamental fish marketing in Makassar, it is found that the existing channels are still efficient, meaning that the marketing channels that occur are still fair, beneficial to cultivators, and do not harm end consumers. Even the profits obtained by the levels of institutions are still fair.